Ullmann's Encyclopedia of Industrial Chemistry 2000
DOI: 10.1002/14356007.b02_21
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Concentration

Abstract: The article contains sections titled: 1. Introduction 2. Principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 1 publication
0
57
0
15
Order By: Relevance
“…Wilfley table is one of key unit operations which can help in diagnostic or amenability of the gravity concentration process for different minerals/ore. The detailed principle of wilfley table has been discussed at different places [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilfley table is one of key unit operations which can help in diagnostic or amenability of the gravity concentration process for different minerals/ore. The detailed principle of wilfley table has been discussed at different places [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Feed characteristics include particle size, density distribution, volumetric flow rate and solid concentration. Similarly the operating parameters include wash water flow rate, deck tilt angle, shake amplitude, shake frequency, splitter position and side tilt angle [3,5,6]. Wilfley table has been used to recover celestite ore [7] and also for the beneficiation of low grade manganese ore [8].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there has been renewed interest in gravity separation techniques, as mining companies move towards more sustainable processes. Burt (1984) stated that the key to effective gravity separation is a good understanding of the ore mineralogical characteristics. He suggested that the following ore mineralogical characteristics be investigated:…”
Section: Gravity Separationmentioning
confidence: 99%
“…Figure 2.11 (Burt, 1984) shows that for -1.180+ 0.212 mm particles a concentration criterion of above 1.8 indicates that the two minerals are separable. In Table 6.1 these values are highlighted in green.…”
Section: 1mentioning
confidence: 99%
“…A amalgamação é um processo altamente sensível aos fatores que afetam a interface ouro-mercúrio, tais como superfícies recobertas por óxidos de ferro, presença de minerais deletérios e de sais de metais básicos, de sulfetos e presença de matéria orgânica (BURT, 1984). É um processo que em larga escala é custoso e pouco eficiente.…”
Section: Formação De Amálgamaunclassified